Generating unfair ratings to attack online rating systems - Neel Ratan Mitra (2014)
Trust plays an emphatic role in any form of transaction, the internet boom in the early 1990s brought in a new era of e-commerce allowing online transactions, reviews as some of the few activities out of many. These activities gave rise to